2008
DOI: 10.1108/14626000810917843
|View full text |Cite
|
Sign up to set email alerts
|

The impact of higher education on entrepreneurial intentions of university students in China

Abstract: Purpose -The aim of this article is to investigate the relationship between Chinese university students' higher educational background and their entrepreneurial intentions. Design/methodology/approach -The TPB model was adopted and tested for the formation of Chinese university students' entrepreneurial intentions using structural equation modeling. Data were collected from students of Tongji University in Shanghai, China. Findings -The main results of this empirical research suggest that diversity of educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
289
7
40

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(365 citation statements)
references
References 36 publications
29
289
7
40
Order By: Relevance
“…A educação formal representa, na maioria dos casos, um importante investimento por parte dos indivíduos, não só porque este tem uma natureza contínua no tempo, como também constitui um meio por meio do qual os indivíduos podem melhorar a sua condição de vida. É possível comprovar empiricamente que, à medida que o nível de educação formal dos indivíduos aumenta, também melhora, na mesma proporção, o seu nível de vida (Wu & Wu, 2008). O impacto do nível de educação alcançado, em particular no domínio dos negócios, predispõe o individuo para uma atitude mais favorável em relação ao empreendedorismo (Le, 1999;Lucas, 1978).…”
Section: Programas Governamentaisunclassified
“…A educação formal representa, na maioria dos casos, um importante investimento por parte dos indivíduos, não só porque este tem uma natureza contínua no tempo, como também constitui um meio por meio do qual os indivíduos podem melhorar a sua condição de vida. É possível comprovar empiricamente que, à medida que o nível de educação formal dos indivíduos aumenta, também melhora, na mesma proporção, o seu nível de vida (Wu & Wu, 2008). O impacto do nível de educação alcançado, em particular no domínio dos negócios, predispõe o individuo para uma atitude mais favorável em relação ao empreendedorismo (Le, 1999;Lucas, 1978).…”
Section: Programas Governamentaisunclassified
“…There are several studies about the impact of entrepreneurial education/training programmes on entrepreneurial behaviour (Turker & Selcuk, 2008;Wu & Wu, 2008;Wang & Wong, 2004). Lee et al (2005) in their cross-cultural research found that young university students are likely to take the step into entrepreneurship if their country can provide customised entrepreneurship education.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Other psychosocial approaches (e.g., Sarasvathy, 2004;Wu & Wu, 2008;Santos et al, 2010;Karabey, 2012;Roxas & Chadee, 2013; admit further that contextual and social factors also act as entrepreneurial behaviour predictors -logically, respecting the individual predisposition. That is, a person potentially entrepreneur may be influenced by economic changes (e.g., increased unemployment), marketing (e.g., emergence of a technology or trend) or individual factors (e.g., training or institutional incentives), and because of that, this person starts a business, as Santos (2008) defended.…”
Section: Entrepreneurial Behaviour Aspectsmentioning
confidence: 99%
“…These studies start from the same point of analysis, the measurement of idiosyncratic behaviours usual among entrepreneurs and the convention that the entrepreneurship is not only linked to the opening of business, but to the individual dispositional traits, related to personality, attitudes, beliefs, interests, values, self-concept, capacity and emotional patterns (Rauch & Frese, 2007;Gelderen et al, 2008;Wu & Wu, 2008;Santos et al, 2009;Schmidt & Bohnenberger, 2009;Nascimento et al, 2010;Obschonka et al, 2010;Alves & Bornia, 2011;Brandstätter, 2011;Abebe, 2012;Karabey, 2012;Minello & Scherer, 2012;Mathieu & St-Jean, 2013;Moraes et al, 2013;Tajeddini et al, 2013;Roxas & Chadee, 2013).…”
Section: Introductionmentioning
confidence: 99%